Synthesis, Characterization, Bioavailability and Antimicrobial Studies of Cefuroxime-Based Organic Salts and Ionic Liquids - Francisco Faísca; Željko Petrovski; Inês Grilo; Sofia A. C. Lima; Miguel M. Santos; Luis C. Branco (MDPI AG, 2024)
Low oral bioavailability is a common feature in most drugs, including antibiotics, due to low solubility in physiological media and inadequate cell permeability, which may limit their efficacy or restrict their administration in a clinical setting. Cefuroxime is usually administered in its prodrug form, cefuroxime axetil. However, its preparation requires further reaction steps and additional metabolic pathways to be converted into its active form. The combination of Active Pharmaceutical Ingredients (APIs) with biocompatible organic molecules as salts is a viable and documented method to improve the solubility and permeability of a drug. Herein, the preparations of five organic salts of cefuroxime as an anion with enhanced physicochemical characteristics have been reported. These were prepared via buffer-assisted neutralization methodology with pyridinium and imidazolium cations in quantitative yields and presented as solids at room temperature. Cell viability studies on 3T3 cells showed that only the cefuroxime salts combined with longer alkyl chain cations possess higher cytotoxicity than the original drug, and while most salts lost in vitro antibacterial activity against E. coli, P. aeruginosa and B. subtilis, one compound, [PyC10Py][CFX]2, retained the activity. Cefuroxime organic salts have a water solubility 8-to-200-times greater than the original drug at 37 °C. The most soluble compounds have a very low octanol-water partition, similar to cefuroxime, while more lipophilic salts partition predominantly to the organic phase.